About what is common. The school and the many. Five lines and one escape (Praxis Educativa, 2018)
In the present article –and as part of  a dialogue on education, with regard to it and for it– we propose to think of the school in its spatio-temporal materiality as a place for meeting others in which the life in common is set. ‘Community’, in this sense, is understood not as a condition, not as an a priori, but as a possibility. ‘The school’ as its opportunity and as a line of flight. In a present marked by uncertainty and loneliness, we propose to think of the school as a space capable of going against the grain, as a spacetime in which dominant modes of relationship can be suspended to build new ones.
Keywords: school; community; encounter; self management; one/many